Taming People’s Power: The EDSA Revolutions and Their Contradictions - Socrates, Maria Celine Anastasia P. (Kasarinlan: Philippine Journal of Third World Studies; Vol 30 No 1 (2015): The 2015 TWSC Writeshop, 2016)
Book review of Claudio, Lisandro E. 2013. Taming People’s Power: The EDSA Revolutions and Their Contradictions. Quezon City: Ateneo de Manila University Press. 226 pp.